Theoretical investigation on generating terahertz radiation from gas plasma induced by three-color ultrashort lasers - 王成亮 杨振刚 刘劲松 汪盛烈 王可嘉 (Chinese physics B, 2015)
Generation of intense broadband terahertz(THz) waves from gas plasma induced by tri-color ultrashort(fundamental(ω), second harmonic(2ω), and third harmonic(3ω)) laser pulses is theoretically investigated. Simulation results show that the 3ω laser pulse can greatly enhance or suppress the generation of THz wave at different values of relative phase(θ 3) between the 3ω and ω fields. Moreover, the polarities of the generated THz waves can be controlled by changing θ 3,with the relative phase θ 2(between the 2ω and ω fields) fixed to be a certain value. All of our results show that θ 3 plays a key role in the generation process, which promises to control the intensity as well as the polarity of gas plasma-induced THz radiation.